Seeds for needs: participatory variety selection - Gevel, Jeske M.J, van de; Gellaw A; Fadda, Carlo (Bioversity International, 2013)
Varietal preference is a carefully weighed balance between consumption and production characteristics. Farmers not only select the high yielding varieties but prefer landraces because of their taste, nutritional value and the ability to grow with fewer inputs. Differences in temperatures, rainfall and length of the grain filling period result in major variations in performance across the three sites. In K’ok’a performance was generally poor compared to Cheffe Donsa and Ejere because of shorter seasons and higher temperatures. In contrast several varieties yielded well in K’ok’a but not in Ejere which is an area that is less stressful in terms of temperature and rainfall. This suggests that most of the good performing varieties hav traits for specific adaptation. We found that locally adapted varieties are the best option for farmers in the three sites. Farmers in Ejera and Cheffe Donsa are able to choose from many accessions due to more favorable environmental conditions. Differences between locally adapted accessions and other categories were highest in K’ok’a which suggests that there is a need for accessions with specific adaptive traits for these suboptimal conditions.